KH HASYIM ASY'ARI'S THOUGHTS ON STUDENT ETHICS IN THE KITAB ADÂB AL-ÂLIM WA AL-MUTA'ALLIM AND ITS RELEVANCE TO THE NATIONAL EDUCATION SYSTEM - Azzam, Zaki Mizanul; Khoir, Mulyanto Abdullah (Proceeding of International Conference of Islamic Education, 2023)
The fading of the character of the nation's children is shown by the increasing actions that have an impact on the destruction of our own nation, such as brawl, murder, rape, and others. This shows that education objectives are not optimal. Whereas the government has drafted a Law on National Education System related to the basis and function of education which refers to the 1945 Constitution and Pancasila, even long before the government designed character education, KH. M. Hasyim Asy'ari had first discussed about character education in his works, both in the book Adab al-‘Alim wa al-Muta‘allim or other books and treatises. Based on the above background, the focus of the problem in this study is the study of KH. M. Hasyim Asy'ari about character education in the book Adâb al-Âlim wa al-Muta'allim is relevant to character education values listed in the National Education System Law. This research method uses a qualitative research model with a literature study approach, while collecting techniques data from various literatures in the form of scientific books, journals, and articles. Data analysis was carried out in a descriptive narrative. The results of this study are as follows: KH. Hasyim Asy'ari about character education in the book Adâb al-Âlim wa al-Muta‘allim is relevant to the National Education System. This was indicated by the character values conveyed by him in his works in accordance with the character values listed in the National Education System.